Technology Acceptance Model (TAM) of Statistical Package for the Social Sciences (SPSS) Applications - Echo Perdana Kusumah (Integrated Journal of Business and Economics (IJBE), 2018)
Department of Management, Faculty of Economics, University of Bangka Belitung has been using SPSS application in the implementation of teaching management subjects, to improve productivity of lecturers work by automating work in the form of SPSS applications. SPSS application aims to provide convenience and acceleration in the process of completion research. This study aims to find out how the user's perception of usefulness and ease of use of SPSS applications. Respondents in this study amounted to 100 students majoring in management. Method of collecting data using electronic questionnaire (google form), measuring tool with 5-point Likert scale, in the validity and reliability test as well analyzed using descriptive analysis by finding the mean value of each item statement. The research model uses Technology Acceptance Model (TAM) with two the main constants are perceived usefulness and perceived ease of use. The results of the discussion show the user perception of the benefits of SPSS application on average overall get the value of Mean with a score of 4.08 and the ease of use SPSS application on average the overall value of Mean score 4.10, so it can be concluded that the respondents get good benefits in using SPSS applications.